Overview of Cellular Immunotherapy for Patients with Glioblastoma - Elodie Vauleon; Tony Avril; Brigitte Collet; Jean Mosser; Véronique Quillien (Clinical and Developmental Immunology)
High grade gliomas (HGG) including glioblastomas (GBM) are the most common and devastating primary brain tumours. Despite important progresses in GBM treatment that currently includes surgery combined to radio- and chemotherapy, GBM patients' prognosis remains very poor. Immunotherapy is one of the new promising therapeutic approaches that can specifically target tumour cells. Such an approach could also maintain long term antitumour responses without inducing neurologic defects. Since the past 25 years, adoptive and active immunotherapies using lymphokine-activated killer cells, cytotoxic T cells, tumour-infiltrating lymphocytes, autologous tumour cells, and dendritic cells have been tested in phase I/II clinical trials with HGG patients. This paper inventories these cellular immunotherapeutic strategies and discusses their efficacy, limits, and future perspectives for optimizing the treatment to achieve clinical benefits for GBM patients.